(untitled) (Research, Society and Development, 2022)
Diabetes Mellitus (DM) is a public health problem, chronic, noncommunicable metabolic disorder caused by multifactors. Diabetic neuropathy is one of the most common complications of DM where the feet are one of the most vulnerable body regions leading to the emergence of lesions, peripheral vascular disease and deformities, called diabetic foot. The performance of nurses plays a fundamental role in the care of users with DM. Exercising between specific functions; the planning and development of actions, with emphasis on educational approaches using the therapeutic doll, aims to report the experience of creating a therapeutic doll as an educational strategy in the prevention and care of diabetic foot. This is an exploratory narrative review, with a qualitative approach with analysis of articles published in databases available in the VHL, Medline, Lilacs and Scielo. Thus from the to create a therapeutic doll as an educational strategy for diabetic foot care and prevention, we obtained a satisfactory result. Effective interventions such as health education and provision of educational materials can improve self-care in individuals with DM, thus preventing a diabetic foot. It was found that the therapeutic doll is a relevant educational strategy aimed at raising awareness of the need for proper daily foot care, bringing positive results for the prevention of diabetic foot complications.